Comorbidities, clinical outcome and rate of herpes simplex positive PCR in patients with keratitis, corneal erosions and ulcers - Mhd Hosam Dandachli; Anna-Karina B. Maier; Jörg Hofmann; Tina Dietrich-Ntoukas (Journal of Ophthalmic Inflammation and Infection)
Abstract Introduction Herpes simplex keratitis (HSK) is a recurrent infection with a high risk of corneal blindness. The aim of the study is to investigate the HSV-PCR-positive smear rate, the ocular and systemic comorbidities and the impact of these comorbidities on the clinical outcome in a group of patients with pathologic corneal findings such as keratitis, persistent epithelial defects and corneal ulcers. Methods In this retrospective study, we recruited 194 eyes who underwent PCR testing for HSV-1 DNA in our tertiary eye clinic from 2015 to 2021 due to suspected HSK. A poor outcome was defined as final visual acuity > 0.4 according to the Logarithm of the Minimum Angle of Resolution (LogMAR) or the need for at least one corneal surgery. Results HSV-1-DNA was detected in 18.6% of the eyes. Corneal scarring (28.8%) and persistent epithelial defects (PED) (8.5%) were the most common complications. The highest recurrence rate (11.6%) was documented 3 months after sampling. 41.2% received systemic antiviral therapy at the first visit after collecting the sample. 75 eyes (38.7%) required at least one corneal surgery, of which amniotic membrane transplantation was the most common corneal procedure in 45 eyes (23.2%). 151 eyes (77.8%) had at least one ocular comorbidity, including previous ocular and corneal procedures (32% and 19.1% respectively) and blepharitis (26.3%). The most common systemic comorbidities were atopic diseases (10.8%), systemic immunosuppression (9.3%) and diabetes mellitus (8.8%). Previous ocular and corneal surgery, glaucoma and diabetes mellitus correlated with a poor outcome (P < 0,001). The average BCVA at the last follow-up (0.76 ± 0.83 LogMAR) was significantly better than at the time of sample collection (0.94 ± 0.76 LogMAR) (P < 0.001). Conclusion Our data confirm that HSK should be treated based on clinical findings regardless of the PCR result. We demonstrate for the first time, that comorbidities are very common and especially previous ocular and corneal surgery, glaucoma and diabetes mellitus are associated with a poor outcome. Although corneal surgery was necessary in almost 40% of the eyes during the follow-up due to a complicated course, a significant overall improvement in visual acuity was achieved compared to the initial findings.